Teacher Knowledge in Transition Planning: Does Locale Matter?. (September 2021) - Deardorff, Malarie E.; Peltier, Corey; Choiseul-Praslin, Belkis; Williams-Diehm, Kendra; Wicker, Melissa
The Individuals With Disabilities Education Act mandates transition planning to occur in conjunction with the individualized education program for secondary age students with disabilities beginning by age 16, or earlier. To fulfill this mandate, teachers must possess a depth of content and pedagogical knowledge related to the transition planning process. However, the majority of special educators do not receive coursework dedicated to transition in their undergraduate programming. Furthermore, teachers in under-resourced and underserved rural districts may have inequitable professional development opportunities to bolster their transition planning knowledge. This lack of transition-related education potentially leads to inadequate and noncompliant transition plans for students with disabilities. The current study examined differences in teachers' knowledge based on locale: rural ( n = 75), suburban ( n = 48), and urban ( n = 64) from one southern state. Determining whether differences are identified by locale can inform the allocation of resources to provide high-quality, evidence-aligned professional development models to improve teacher knowledge in underserved and under-resourced rural locales. In addition, identifying gaps in teacher knowledge will inform pre-service and in-service teacher preparation. We provide an avenue of needed future research to improve transition-planning processes for students with disabilities.